Kajian Hidrolika Sungai Kusan Kabupaten Tanah Bumbu Provinsi Kalimantan Selatan Dengan Uji Model Fisik dengan Skala Distorsi Vertikal 1:40 Horizontal 1:80 - Danudoro, Muhammad; Dermawan, Very; Wahyuni, Sri (Fakultas Teknik, Universitas Brawijaya, 2021)
The research was conducted to determine the hydraulic conditions in the Kusan River by means of a modeled prototype which would later be compared with the theoretical calculation results. Discharge test with a rating curve on the river model of the Kusan River with distortion scale of vertical 1:40 horizontal 1:80. To decide which sediment that will be used to do test on model, it takes several sample of sediment test when testing the river model. There are 5 samples tested, with a ratio of sand and coal, those ratio sample between sand and coal are 1: 9, 2: 8, 3: 7, 4: 6 and 5: 5, referring to the ratio of 3: 7 as the best criterion. The estimation of the passing discharge in the existing by calculating of the rating curve in several sections of the Kusan River by using a slope of 0.007007 (mean slope) and n manning 0.03. From the winding discharge, it is determined that the discharge used is a small discharge with a water level of ± 0.50 (14.29 m3/s), a medium discharge with a water level of ± 2.00 m (156.07 m3/s) and a large discharge with a water level. ± 3.50 m (519.64 m3/s). Penelitian tersebut dilakukan untuk mengetahui kondisi hidrolika di Sungai Kusan secara prototype yang dimodelkan yang nantinya dibandingan dengan hasil perhitungan teori. Dengan debit pengujian dilakukan menggunakan rating curve pada sungai model Sungai Kusan dengan skala distorsi vertical 1:40 horisontal 1:80. Diperlukan pengujian terhadap bebeara sampel sedimen yang bertujuan untuk menentukan sedimen yang nantinya akan digunakan saat pengujian model sungai. Terdapat 5 sampel yang diujikan, dengan perbandingan jumlah pasir dan jumlah batu bara 1:9, 2:8, 3:7, 4:6 dan 5:5, mengacu pada perbandingan 3:7 sebagai kriteria yang paling baik. Estimasi debit yang lewat pada kondisi eksisting adalah dengan perhitungan lengkung debit pada beberapa section Sungai Kusan dengan menggunakan slope 0,007007 (slope rerata) dan n manning 0,03. Dari liku debit ditentukan debit yang digunakan adalah debit kecil dengan ketinggian air ± 0,50 m (14,29 m3/detik), debit sedang dengan ketinggian air ± 2,00 m (156,07 m3/detik) dan debit besar dengan ketinggian air ± 3,50 m (519,64 m3/detik).